Water monsters : opposing viewpoints - Garinger, Alan, 1932- (San Diego, Calif. : Greenhaven Press, 1991)
Explores the reports and evidence for the existence of mysterious large creatures allegedly living in certain lakes and rivers of the United States.
Includes bibliographical references (p. 91) and index.
Wilson's Junior High School.
7.7
5-8
Keywords: Sea monsters -- United States -- Juvenile literature; Sea monsters; Sea monsters